Perancangan Corporate Identity Kampoeng Banyumili di Desa Gedangan - Dimas Prastowo Aji; Peni Pratiwi; Birmanti Setya Utami (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2019)
Kampoeng Banyumili is one of many new tourist attraction located in Jl. Raya Muncul-Salatiga KM.5 Desa Gedangan, Kabupaten Semarang, Central Java that haven't implemented a consistent corporate identity. There are 3 different logos that are being used stimultaneously in Kampoeng Banyumili. Corporate identity is important to bring out company's certain image. Deep reaserach on client is a must when designing Corporate identity to match the image a company desired and making it easier to combine logos, colors, typographys, and graphic elements so it will matched the concept. Based on SWOT analysis and target audience on designing Kampoeng Banyumili corporate identity, the concept of shape, color, typography, and graphic elements is to give a natural image, simple, elegant, and togetherness. The design result are logos and graphic elements as an identity and supporting media to help Kampoeng Banyumili introduced the new image and identity to public that is easy to remember and to gain public's trust. Key Words : Kampoeng Banyumili, Corporate Identity, Logo, Graphic Element